'We are doing better': Biopolitical nationalism and the COVID-19 virus in East Asia. (August 2020) - Kloet, Jeroen de; Lin, Jian; Chow, Yiu Fai
The COVID-19 pandemic stirs up strong nationalist and localist sentiments; places pride themselves on containing the virus more effectively: We are doing better. We call this 'biopolitical nationalism', understood by us as the dynamics between body, geopolitics and affect. When looking at mainland China, Taiwan and Hong Kong, we analyse how the biopolitical efforts of these places are being compared, applauded and supported. Under a discourse of life and survival, this celebration of biopolitical control does not fall into the classic reproduction of capital, but speaks to geopolitical identification. Biopolitics has morphed into a field of competition, of rivalry, of nationalistic – or, perhaps more generally, localist – power games. What can we do as Cultural Studies scholars?